Ultrasound-induced emission material as well as preparation method and application thereof

By preparing the ultrasonic induced luminescent material Li1-xTaO3:xTb3+, combined with ultrasonic induced luminescence technology, the damage problem of traditional luminescence on the material is solved, and efficient and accurate detection of internal defects and stress distribution of non-destructive detection of the material is achieved.

CN120464393APending Publication Date: 2025-08-12CHINA UNIV OF GEOSCIENCES (WUHAN) +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510433564.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-08
Publication Date
2025-08-12

AI Technical Summary

Technical Problem

In the prior art, traditional excitation methods of force-induced luminescence usually cause irreversible damage to the material, lacking effective methods for detecting internal defects and stress distribution of materials in non-destructive materials, and ultrasonic induced luminescent material systems are relatively scarce.

Method used

An ultrasonic induced luminescent material Li1-xTaO3:xTb3+ was developed, and the damage detection was performed by calcining high-purity Li2CO3, Ta2O5, Tb4O7 and H3BO3 at 800-1400°C and mixing it with epoxy resin to form a coating layer, and ultrasonic induced luminescence was used for damage detection.

Benefits of technology

It realizes contactless and precisely controlled force-luminescence detection, providing high-precision damage detection means, suitable for non-destructive detection of flexible devices, engineering devices and biological tissues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120464393A_ABST
    Figure CN120464393A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ultrasound-induced emission materials, in particular to an ultrasound-induced emission material and a preparation method and application thereof. The chemical formula of the ultrasonic induced emission material is Li (1-x) TaO3: xTb < 3 + >, and x is greater than or equal to 0 and less than or equal to 0.2. The damage detection method based on ultrasonic-induced emission comprises the following steps: coating a substrate to be detected with the ultrasonic-induced emission material to form a coating layer, performing ultrasonic action on the substrate, inducing the coating layer to emit light, and judging the damage degree of the substrate according to a light-emitting image. Ultrasonic waves are used as a stressor to induce LiTaO3: Tb < 3 + > to emit light, the cavitation effect generated by the ultrasonic waves in the LiTaO3: Tb < 3 + > material is combined with the ultrasonic waves to induce luminescence generated by overflowing of carriers in traps on the surface of the material, the ultrasonic waves have the advantages of being non-contact and capable of accurately controlling parameters, and a brand new means is provided for researching mechanoluminescence.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ultrasound-induced luminescence materials, and in particular to an ultrasound-induced luminescence material and a preparation method and application thereof. Background Art

[0002] Mechanoluminescence (MEL) is the phenomenon in which mechanical forces (such as stretching, compression, bending, and friction) act on a material surface to produce luminescence. MEL enables the detection and optical visualization of mechanical strain in a wide range of applications, from biophysical stress monitoring to material testing, labeling, and data encryption. However, conventional MEL excitation methods typically involve direct mechanical force acting on the material surface, which often causes irreversible damage. Therefore, developing non-destructive MEL methods is crucial for continuous stress detection during long-term use. Ultrasound can be used to achieve contactless, remote stimulation, even penetrating aqueous media, biological tissue, and other materials. When luminescence is induced by ultrasound (called ultrasound-induced luminescence (USL)), it opens up a whole new range of applications. For example, it can be used to detect internal defects and stress distribution in materials, providing a basis for quality control and reliability assessment. In the biomedical field, USL can be used for imaging and diagnosis of biological tissues, such as detecting tumors and monitoring tissue stress changes. Sensors based on USL can be used to measure physical quantities such as stress, pressure, and temperature, and have broad application prospects.

[0003] While ultrasound-induced luminescence (UIL) offers numerous advantages, research in this field remains in a phase of continuous development and exploration. Since the concept of UIL was first proposed, relatively few mature UIL systems have been reported, and most of these are organic UIL materials. Therefore, the development of novel inorganic UIL materials is of great significance. Summary of the Invention

[0004] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to provide an ultrasound-induced luminescence material and a preparation method and application thereof.

[0005] The first object of the present invention is to provide an ultrasound-induced luminescence material having the chemical formula Li 1-x TaO3:xTb 3+ , where 0≤x≤0.2.

[0006] Furthermore, x is 0.006.

[0007] A second object of the present invention is to provide a method for preparing the ultrasonic induced luminescence material as described above, comprising grinding high-purity Li2CO3, Ta2O5, Tb4O7 and H3BO3 in a mortar to obtain an initial mixed raw material; calcining the mixed powder at a temperature of 800-1400°C in an air atmosphere for 6-12 hours, cooling to room temperature, and grinding the mixed powder to obtain the ultrasonic induced luminescence material.

[0008] Furthermore, the molar ratio of Li, Ta and Tb is 1-x:1:x, 0≤x≤0.2; wherein, the mass excess of Li2CO3 is 5%-15%; and H3BO3 is used as a flux, the mass of which is 1%-5% of the total mass of other raw materials.

[0009] The third object of the present invention is to provide a damage detection method using ultrasonic induced luminescence, in which the above-mentioned ultrasonic induced luminescence material is coated on the substrate to be detected to form a coating layer, ultrasound acts on the substrate and induces the coating layer to emit light, and the degree of damage to the substrate is determined based on the luminescent image.

[0010] Furthermore, the ultrasound-induced luminescence material is mixed with epoxy resin and then coated on the substrate to be detected to form a coating layer.

[0011] Furthermore, the mass ratio of the ultrasound-induced luminescence material to the epoxy resin is 0.1-1.5:0.5.

[0012] Furthermore, the mass ratio of the ultrasound-induced luminescence material to the epoxy resin is 0.75:0.5.

[0013] Furthermore, the substrate is a flexible device, an engineering device, a biological body or a tissue.

[0014] Furthermore, the ultrasonic output power is not less than 0.11W / cm 2 .

[0015] Beneficial effects of the present invention:

[0016] (1) Using ultrasound as a stress source to induce LiTaO3:Tb 3+ Luminescence, Ultrasonic Waves in LiTaO3:Tb 3+ The cavitation effect generated inside the material is combined with the luminescence produced by the overflow of carriers in the traps on the surface of the material induced by ultrasound. Compared with traditional mechanical stress excitation methods (such as extrusion, stretching, friction, etc.), ultrasound has the advantages of being non-contact and having precise control over parameters (frequency, power, action time, etc.). It can achieve uniform stress loading on the luminescent material without destroying the sample, providing a new means for studying mechanoluminescence.

[0017] (2) The intensity of ultrasonic induced luminescence is controlled by adjusting the mixing ratio of the luminescent material and the epoxy resin and the output power of the ultrasonic wave. The optimal emission peak of the emission spectrum is located at 550nm, which belongs to the visible light region and presents green light.

[0018] (3) The present invention proposes a simpler thin-film damage detection technology. This damage detection method based on ultrasound-induced luminescence has the advantages of high definition and high efficiency, and can provide innovative damage detection methods for flexible devices, biomechanics, engineering flaw detection and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Li prepared in Examples 2, 3, 5-11, and 15 1-x TaO3:xTb 3+ (0.002≤x≤0.2)Ultrasound-induced luminescence image of phosphor;

[0020] Figure 2 Li prepared in Examples 2, 3, 5-11, and 15 1-x TaO3:xTb 3+ (0.002≤x≤0.2) Ultrasonic induced luminescence intensity diagram of phosphor;

[0021] Figure 3 LiTaO3 and Li prepared in Examples 1 and 15 0.994 TaO3:0.6%Tb 3+ XRD pattern of

[0022] Figure 4 Li prepared in Example 15 0.994 TaO3:0.6%Tb 3+ Topography;

[0023] Figure 5 Ultrasonic induced luminescence image of a wafer prepared by mixing the luminescent material and epoxy resin in Example 15;

[0024] Figure 6 Ultrasound-induced luminescence images of the hybrid discs prepared in Examples 1, 4, and 12-17;

[0025] Figure 7 Luminescent image showing the change in ultrasound-induced luminescence intensity of a wafer prepared by mixing the luminescent material and epoxy resin in Example 15 with increasing ultrasonic output power;

[0026] Figure 8 The photoluminescence, afterglow luminescence, mechanoluminescence and ultrasound-induced luminescence spectra of the luminescent material of Example 15;

[0027] Figure 9Ultrasound-induced luminescence images of the hybrid discs prepared in Examples 15, 18, 19, and 20;

[0028] Figure 10 This is the ultrasound-induced luminescence curve of the hybrid disc prepared in Example 15;

[0029] Figure 11 Thermoluminescence curve and peak analysis of the powder sample prepared in Example 15;

[0030] Figure 12 Thermoluminescence curve peaks of the powder sample prepared in Example 15 at different waiting times were fitted and the trap depth was calculated;

[0031] Figure 13 The damage detection application diagram of the powder sample prepared in Example 15 and then painted on the surface of different damaged materials after combining with epoxy resin. DETAILED DESCRIPTION

[0032] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.

[0033] Example 1

[0034] The chemical formula of the perovskite structure of this example is LiTaO3; its preparation method includes the following steps:

[0035] (1) High-purity Li2CO3, Ta2O5, and H3BO3 are fully ground in a mortar to obtain an initial mixed raw material. No rare earth ions are doped, and H3BO3 accounts for 2% of the total mass of the other raw materials.

[0036] (2) The mixed powder sample of step (1) was calcined at 1050° C. in an air atmosphere for 8 h, cooled to room temperature, and fully ground to obtain a powder.

[0037] (3) The obtained powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.75:0.5 g.

[0038] Example 2

[0039] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.998 TaO3:0.2%Tb 3+ ; Its preparation method comprises the following steps:

[0040] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb was 0.998:1:0.002, the mass excess of Li2CO3 was 10%, and the mass of H3BO3 was 2% of the total mass of the other raw materials.

[0041] (2) The mixed powder sample of step (1) was calcined at a temperature of 1050° C. in an air atmosphere for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0042] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.75:0.5 g.

[0043] Tb 3+ Tb doped in LiTaO3 matrix 3+ As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0044] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0045] Example 3

[0046] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.996 TaO3:0.4%Tb 3+ ; Its preparation method comprises the following steps:

[0047] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb was 0.996:1:0.004, the mass excess of Li2CO3 was 10%, and the mass of H3BO3 was 2% of the total mass of the other raw materials.

[0048] (2) The mixed powder sample of step (1) was placed at a temperature of 1050° C. in an air atmosphere and calcined for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0049] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.75:0.5 g.

[0050] Tb 3+ Tb doped in LiTaO3 matrix 3+As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0051] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0052] Example 4

[0053] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.994 TaO3:0.6%Tb 3+ ; Its preparation method comprises the following steps:

[0054] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb was 0.994:1:0.006, the mass excess of Li2CO3 was 10%, and the mass of H3BO3 was 2% of the total mass of the other raw materials.

[0055] (2) The mixed powder sample of step (1) was placed at a temperature of 1050° C. in an air atmosphere and calcined for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0056] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.05:0.5 g.

[0057] Tb 3+ Tb doped in LiTaO3 matrix 3+ As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0058] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0059] Example 5

[0060] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.988 TaO3:1.2%Tb 3+ ; Its preparation method comprises the following steps:

[0061] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb was 0.988:1:0.012, the mass excess of Li2CO3 was 10%, and the mass of H3BO3 was 2% of the total mass of the other raw materials.

[0062] (2) The mixed powder sample of step (1) was placed at a temperature of 1050° C. in an air atmosphere and calcined for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0063] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.75:0.5 g.

[0064] Tb 3+ Tb doped in LiTaO3 matrix 3+ As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0065] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0066] Example 6

[0067] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.97 TaO3:3%Tb 3+ ; Its preparation method comprises the following steps:

[0068] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb was 0.97:1:0.03, the mass excess of Li2CO3 was 10%, and the mass of H3BO3 was 2% of the total mass of the other raw materials.

[0069] (2) The mixed powder sample of step (1) was placed at a temperature of 1050° C. in an air atmosphere and calcined for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0070] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.75:0.5 g.

[0071] Tb 3+ Tb doped in LiTaO3 matrix 3+As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0072] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0073] Example 7

[0074] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.95 TaO3:5%Tb 3+ ; Its preparation method comprises the following steps:

[0075] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 are thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb is 0.95:1:0.05, the mass excess of Li2CO3 is 10%, and the mass of H3BO3 is 2% of the total mass of the other raw materials.

[0076] (2) The mixed powder sample of step (1) was placed at a temperature of 1050° C. in an air atmosphere and calcined for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0077] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.75:0.5 g.

[0078] Tb 3+ Tb doped in LiTaO3 matrix 3+ As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0079] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0080] Example 8

[0081] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.93 TaO3:7%Tb 3+ ; Its preparation method comprises the following steps:

[0082] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb was 0.93:1:0.07, the mass excess of Li2CO3 was 10%, and the mass of H3BO3 was 2% of the total mass of the other raw materials.

[0083] (2) The mixed powder sample of step (1) was placed at a temperature of 1050° C. in an air atmosphere and calcined for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0084] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.75:0.5 g.

[0085] Tb 3+ Tb doped in LiTaO3 matrix 3+ As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0086] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0087] Example 9

[0088] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.9 TaO3:10%Tb 3+ ; Its preparation method comprises the following steps:

[0089] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb was 0.9:1:0.1, the mass excess of Li2CO3 was 10%, and the mass of H3BO3 was 2% of the total mass of the other raw materials.

[0090] (2) The mixed powder sample of step (1) was placed at a temperature of 1050° C. in an air atmosphere and calcined for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0091] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.75:0.5 g.

[0092] Tb 3+ Tb doped in LiTaO3 matrix 3+As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0093] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0094] Example 10

[0095] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.85 TaO3:15%Tb 3+ ; Its preparation method comprises the following steps:

[0096] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb was 0.85:1:0.15, the mass excess of Li2CO3 was 10%, and the mass of H3BO3 was 2% of the total mass of the other raw materials.

[0097] (2) The mixed powder sample of step (1) was placed at a temperature of 1050° C. in an air atmosphere and calcined for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0098] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.75:0.5 g.

[0099] Tb 3+ Tb doped in LiTaO3 matrix 3+ As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0100] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0101] Example 11

[0102] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.8 TaO3:20%Tb 3+ ; Its preparation method comprises the following steps:

[0103] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb was 0.8:1:0.2, the mass excess of Li2CO3 was 10%, and the mass of H3BO3 was 2% of the total mass of the other raw materials.

[0104] (2) The mixed powder sample of step (1) was placed at a temperature of 1050° C. in an air atmosphere and calcined for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0105] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.75:0.5 g.

[0106] Tb 3+ Tb doped in LiTaO3 matrix 3+ As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0107] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0108] Example 12

[0109] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.994 TaO3:0.6%Tb 3+ ; Its preparation method comprises the following steps:

[0110] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb was 0.994:1:0.006, the mass excess of Li2CO3 was 10%, and the mass of H3BO3 was 2% of the total mass of the other raw materials.

[0111] (2) The mixed powder sample of step (1) was placed at a temperature of 1050° C. in an air atmosphere and calcined for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0112] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.1:0.5 g.

[0113] Tb 3+ Tb doped in LiTaO3 matrix 3+As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0114] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0115] Example 13

[0116] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.994 TaO3:0.6%Tb 3+ ; Its preparation method comprises the following steps:

[0117] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb was 0.994:1:0.006, the mass excess of Li2CO3 was 10%, and the mass of H3BO3 was 2% of the total mass of the other raw materials.

[0118] (2) The mixed powder sample of step (1) was placed at a temperature of 1050° C. in an air atmosphere and calcined for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0119] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.25:0.5 g.

[0120] Tb 3+ Tb doped in LiTaO3 matrix 3+ As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0121] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0122] Example 14

[0123] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.994 TaO3:0.6%Tb 3+ ; Its preparation method comprises the following steps:

[0124] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb was 0.994:1:0.006, the mass excess of Li2CO3 was 10%, and the mass of H3BO3 was 2% of the total mass of the other raw materials.

[0125] (2) The mixed powder sample of step (1) was placed at a temperature of 1050° C. in an air atmosphere and calcined for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0126] (3) The obtained ultrasonic induced luminescence powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescence powder to the epoxy resin was 0.5:0.5 g.

[0127] Tb 3+ Tb doped in LiTaO3 matrix 3+ As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0128] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0129] Example 15

[0130] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.994 TaO3:0.6%Tb 3+ ; Its preparation method comprises the following steps:

[0131] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb was 0.994:1:0.006, the mass excess of Li2CO3 was 10%, and the mass of H3BO3 was 2% of the total mass of the other raw materials.

[0132] (2) The mixed powder sample of step (1) was placed at a temperature of 1050° C. in an air atmosphere and calcined for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0133] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.75:0.5 g.

[0134] Tb 3+ Tb doped in LiTaO3 matrix 3+As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0135] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0136] Example 16

[0137] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.994 TaO3:0.6%Tb 3+ ; Its preparation method comprises the following steps:

[0138] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb was 0.994:1:0.006, the mass excess of Li2CO3 was 10%, and the mass of H3BO3 was 2% of the total mass of the other raw materials.

[0139] (2) The mixed powder sample of step (1) was placed at a temperature of 1050° C. in an air atmosphere and calcined for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0140] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material, and the mass ratio of the luminescent powder to the epoxy resin was 1:0.5 g.

[0141] Tb 3+ Tb doped in LiTaO3 matrix 3+ As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0142] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0143] Example 17

[0144] The ultrasonic induced luminescence material of the perovskite structure in this example has the chemical formula Li 0.994 TaO3:0.6%Tb 3+ ; Its preparation method comprises the following steps:

[0145] (1) High-purity Li2CO3, Ta2O5, Tb4O7, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material. The molar ratio of Li, Ta, and Tb was 0.994:1:0.006, the mass excess of Li2CO3 was 10%, and the mass of H3BO3 was 2% of the total mass of the other raw materials.

[0146] (2) The mixed powder sample of step (1) was placed at a temperature of 1050° C. in an air atmosphere and calcined for 8 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0147] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 1.5:0.5 g.

[0148] Tb 3+ Tb doped in LiTaO3 matrix 3+ As the luminescent center, a phosphor powder emitting green light is formed, and the powder is compounded with an optical epoxy resin to obtain an ultrasonic induced luminescence material emitting green light.

[0149] The ultrasound-induced luminescence material of this embodiment can achieve repeatable ultrasound-induced luminescence after pre-irradiation under ultraviolet light.

[0150] Example 18

[0151] The ultrasonic induced luminescence material of this embodiment has the chemical formula Zn 0.99 S:1%Cu 2+ ; Its preparation method comprises the following steps:

[0152] (1) High-purity ZnS, CuO, and H3BO3 were fully ground in a mortar to obtain an initial mixed raw material, wherein the molar ratio of Zn to Cu was 0.99:0.01, and H3BO3 accounted for 2% of the total mass of the other raw materials.

[0153] (2) The mixed powder sample of step (1) was placed at a temperature of 1100° C. in an air atmosphere and calcined for 6 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0154] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.75:0.5 g.

[0155] Cu 2+ When doped into the ZnS matrix, a luminescent material with long green afterglow is formed.

[0156] The luminescent material of this embodiment can achieve long afterglow luminescence after pre-irradiation under ultraviolet light, and can generate mechanoluminescence after mechanical force is applied, but basically no ultrasonic induced luminescence.

[0157] Example 19

[0158] The ultrasonic induced luminescence material of this embodiment has the chemical formula Sr 2.98 Sn2O7:2%Sm 3+ ; Its preparation method comprises the following steps:

[0159] (1) High-purity SrCO3, SnO2, Sm2O3, and H3BO3 were fully ground in a mortar to obtain an initial mixed raw material, wherein the molar ratio of Sr, Sn, and Sm was 2.98:2:0.02, and H3BO3 accounted for 2% of the total mass of the other raw materials.

[0160] (2) The mixed powder sample of step (1) was pre-fired at a temperature of 800°C in an air atmosphere for 1 hour, cooled to room temperature, fully ground and sintered again, and then pre-fired at a temperature of 1350°C in an air atmosphere for 6 hours, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0161] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.75:0.5 g.

[0162] Sm 3+ When doped into the Sr3Sn2O7 matrix, a luminescent material with mechanoluminescence is formed.

[0163] The luminescent material of this embodiment can generate mechanoluminescence after being pre-irradiated under ultraviolet light and mechanical force is applied, but has substantially no ultrasonically induced luminescence.

[0164] Example 20

[0165] The ultrasonic induced luminescence material of this embodiment has the chemical formula of CaZn 0.997 OS:0.3%Mn 2+ ; Its preparation method comprises the following steps:

[0166] (1) High-purity CaCO3, ZnS, MnCO3, and H3BO3 were thoroughly ground in a mortar to obtain an initial mixed raw material, wherein the molar ratio of Ca, Zn, S, and Mn was 1:0.997:1:0.003, and H3BO3 accounted for 2% of the total mass of the other raw materials.

[0167] (2) The mixed powder sample of step (1) was placed at a temperature of 1100° C. and calcined in a nitrogen atmosphere for 3 h, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence powder.

[0168] (3) The obtained ultrasonic induced luminescent powder and optical epoxy resin were compounded using a plastic mold with a diameter of 25 mm and a thickness of 10 mm to prepare a disc composite material. The mass ratio of the luminescent powder to the epoxy resin was 0.75:0.5 g.

[0169] Mn 2+ When incorporated into the CaZnOS matrix, a luminescent material with mechanoluminescence is formed.

[0170] The luminescent material of this embodiment can generate mechanoluminescence after being pre-irradiated under ultraviolet light and mechanical force is applied, but has substantially no ultrasonically induced luminescence.

[0171] Figure 1 Li prepared in Examples 2, 3, 5-11, and 15 1-x TaO3:xTb 3+ Ultrasonic induced luminescence image of (0.002≤x≤0.2) phosphor, the luminescence is concentrated in the center of the disc, Tb 3+ The optimal doping concentration is x=0.006.

[0172] Figure 2 Li prepared in Examples 2, 3, 5-11, and 15 1-x TaO3:xTb 3+ The ultrasound-induced luminescence intensity diagram of the (0.002≤x≤0.2) phosphor shows a trend of first increasing and then decreasing, with the intensity peak at x=0.006.

[0173] Figure 3 LiTaO3 and Li prepared in Examples 1 and 15 0.994 TaO3:0.6%Tb 3+ The XRD pattern of the synthesized LiTaO3 and Li 0.994 TaO3:0.6%Tb 3+ All are pure phase.

[0174] Figure 4 Li prepared in Example 15 0.994 TaO3:0.6%Tb 3+ Morphology diagram, the sample size is 500-900nm spherical, and there is a certain agglomeration phenomenon.

[0175] Figure 5 This is an ultrasound-induced luminescence image of a disc made by mixing the luminescent material and epoxy resin in Example 15. As the ultrasonic excitation time increases, the intensity of the ultrasound-induced luminescence gradually increases, reaching a peak and then stabilizing. The luminescence gradually spreads from the center of the disc to the edge.

[0176] Figure 6 Ultrasonic induced luminescence (UIL) images of the hybrid discs prepared in Examples 1, 4, and 12-17. By adjusting the mixing ratio of the luminescent material to the epoxy resin, the UIL intensity of the material first increases and then decreases. The optimal mixing ratio is 0.75g luminescent material: 0.5g epoxy resin.

[0177] Figure 7 Luminescent image showing the change in ultrasonic induced luminescence intensity with increasing ultrasonic output power for the preparation of a disc made by mixing the luminescent material with epoxy resin in Example 15. As the ultrasonic output power gradually increases, the ultrasonic induced luminescence intensity of the material gradually increases.

[0178] Figure 8 The photoluminescence, afterglow luminescence, mechanoluminescence and ultrasound-induced luminescence spectra of the luminescent material of Example 15 are shown. Comparing the different spectra of the luminescent material, it is found that the four spectral curves are basically consistent, proving that the luminescence center originates from the same position.

[0179] Figure 9 Ultrasonic induced luminescence images of the mixed discs prepared in Examples 15, 18, 19, and 20. Under the same test conditions, LiTaO3:Tb 3+ The material showed obvious ultrasound-induced luminescence phenomenon, ZnS:Cu 2+ The material exhibits obvious afterglow luminescence, Sr3Sn2O7:Sm 3+ 、CaZnOS:Mn 2+ The materials showed no obvious luminescence. Under the same synthesis conditions, only LiTaO3:Tb 3+ The material exhibits obvious ultrasound-induced luminescence.

[0180] Figure 10 This is the UIL curve of the hybrid disc prepared in Example 15. The UIL performance was tested after waiting for different periods of time under the same UV pre-irradiation time. As the waiting time increased, the UIL curve gradually stabilized.

[0181] Figure 11 Thermoluminescence (TEL) curves and peak separations of the powder samples prepared in Example 15. Under the same UV pre-irradiation time, longer waiting times resulted in lower TEL peaks, and the low-temperature (320K) peak gradually disappeared. Furthermore, each TEL curve can be divided into three peaks, demonstrating the presence of three distinct traps within the material.

[0182] Figure 12Thermoluminescence curve peaks of the powder sample at different waiting times were prepared for Example 15, and the trap depths were calculated by fitting. As the waiting time increased, trap I gradually disappeared, while traps II and III gradually stabilized.

[0183] Figure 13 Figures show damage detection applications using powder samples prepared in Example 15, combined with epoxy resin, and then applied to various damaged surfaces. Figure (i) shows aluminum alloy discs with three different types of damage; Figure (ii) shows a mixed sample applied using screen printing on the surfaces of discs with different types of damage; and Figure (iii) shows the luminescence image of the material after ultrasound application. The film on the aluminum alloy disc exhibits strong luminescence in the damaged areas, and the shape of the luminescence matches the shape of the damage on the disc.

[0184] Any matters not mentioned above shall be subject to the existing technology.

[0185] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art of the present invention may make various modifications or additions to the described specific embodiments or replace them in similar ways, but they will not deviate from the direction of the present invention or exceed the scope defined by the appended claims. Those skilled in the art should understand that any modifications, equivalent replacements, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the scope of protection of the present invention.

Claims

1. An ultrasound-induced luminescence material, characterized in that: The chemical formula is Li 1-x TaO3:xTb 3+ , where 0≤x≤0.

2.

2. The ultrasound-induced luminescence material according to claim 1, wherein: x is 0.

006.

3. A method for preparing the ultrasound-induced luminescence material according to claim 1 or 2, characterized in that: High-purity Li2CO3, Ta2O5, Tb4O7 and H3BO3 are fully ground in a mortar to obtain an initial mixed raw material; the mixed powder is placed at a temperature of 800-1400°C and calcined in an air atmosphere for 6-12 hours, cooled to room temperature, and fully ground to obtain an ultrasonic induced luminescence material.

4. The preparation method according to claim 3, wherein The molar ratio of Li, Ta and Tb is 1-x:1:x, 0≤x≤0.2; wherein, the mass excess of Li2CO3 is 5%-15%; and H3BO3 is used as a flux, the mass of which is 1%-5% of the total mass of other raw materials.

5. A damage detection method using ultrasound-induced luminescence, characterized in that: The ultrasonic induced luminescence material according to claim 1 or 2 is coated on a substrate to be inspected to form a coating layer. Ultrasound acts on the substrate to induce the coating layer to emit light. The degree of damage to the substrate is determined based on the luminescent image.

6. The damage detection method using ultrasound-induced luminescence according to claim 5, wherein: The ultrasonic induced luminescence material is mixed with epoxy resin and then coated on a substrate to be detected to form a coating layer.

7. The damage detection method using ultrasound-induced luminescence according to claim 5, wherein: The mass ratio of the ultrasound-induced luminescence material to the epoxy resin is 0.1-1.5:0.

5.

8. The damage detection method using ultrasound-induced luminescence according to claim 5, wherein: The mass ratio of ultrasound-induced luminescence material to epoxy resin is 0.75:0.

5.

9. The damage detection method using ultrasound-induced luminescence according to claim 5, wherein: The substrate is a flexible device, an engineering device, a biological body or a tissue.

10. The damage detection method using ultrasound-induced luminescence according to claim 5, wherein: Ultrasonic output power is not less than 0.11W / cm 2 .